Group Discussion and Booklet for Tuberculosis Prevention in Manado - Elne Vieke Rambi; Ketrina Konoralma; Dionysius Sumenge (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
The purpose of the study was to determine the effect of using focus group discussions and booklets for the prevention of tuberculosis in Manado. Type of Research